EVALUATION OF GENETIC RISK FACTORS FOR CHILDHOOD ASTHMA USING GENERALIZED MULTIFACTOR DIMENSIONALITY REDUCTION SOFTWARE - Olga Cirstea; Liubov Vasilos; Ala Cojocaru; Dorina Savoschin (Amaltea Medical Publishing House, 2014)
Asthma is a multifactorial disease caused by numerous genetic interrelations and also gene-environment interactions. Traditional statistical methods applied for case-control studies in do not offer the possibility for in-depth analysis of the genetic risk because of the "dimensionality" problem. The Generalized Multifactor Dimensionality Reduction software was successfully applied in genetic studies of cancer, hypertension, diabetes, etc. The aim of our study was to use the GMDR software to analyze the role of genetic interrelations on asthma development in Moldovan children. Materials and methods. The case-control study included 180 children: 90 children with asthma and 90 healthy controls comparable by age and gender. The GMDR software Beta 0,9 was applied to adjust for discrete quantitative data and covariates. Association of genetic polymorphisms (GSTТ1 and GSTM1 gene deletions; GSTP1 313 A > G; NAT2 481 C > T, 590 G > A and 857 G > A; IL-4 -590 C > T, IL-4Rα Arg551Gln; TNFα -308 G > A; (ААТ)n repetitions in intron 20 of the NOS1 gene; and CC16 38 G > A) with the risk of developing asthma was studied. Results. Data analysis using the GMDR method resulted with identifi cation of a combination of four genotypes (GSTT1+, NAT2 *5-*7/*5-*7, NOS1 <12/>12, and IL-4 -590 C/C) that increases by 3.6 folds the risk of childhood asthma development (OR = 3.61; CI 95% 1,45-8,99; p < 0,01). Conclusions. Gene-gene interactions interfere at different levels of pathophysiological mechanisms of childhood asthma development. Analysis of the interaction models generated by the GMDR software based on study data showed a signifi cant association between asthma risk and polymorphisms in two important groups of genes - xenobiotic-metabolizing genes and the gene responsible for nitric oxide synthesis in airway mucosa.